Strengthening Islamic Communication Ethics in Premarital Guidance Services at the Muara Sipongi Office of Religious Affairs (KUA) through a Local Cultural Approach - Kholilah, Ummi; Ritonga, Elfi Yanti (LP2M INSURI Ponorogo, 2025)
This study explores the integration of Islamic communication principles with local cultural traditions in premarital guidance at the Office of Religious Affairs (KUA) Muara Sipongi, Mandailing Natal. The purpose of this research is to analyze how qaulan sadiidan, qaulan layyinan, qaulan kariman, and qaulan balighan are applied in counseling sessions. Using a qualitative approach with a Participatory Action Research (PAR) design, the partners involved were four pairs of prospective brides and grooms, two religious counselors, and the Head of the KUA. Data were collected through observation, interviews, and documentation, and analyzed thematically with triangulation. The results show that the integration of Islamic communication with local traditions such as sumando and manjujur enriched the counseling process and made it more contextual. Participants also demonstrated increased knowledge: initially limited in understanding Islamic communication, after the sessions they could explain and apply the concepts in marital contexts. This study concludes that premarital guidance becomes more effective when Islamic values are combined with cultural wisdom, offering a contextual model for other regions.